Development of a Maintenance Management System for Primary Machinery to Enhance Productivity: A Case Study of Technology Development Workshops - Auya, Samwel; Bor, Erick (Journal of Research in Science and Engineering, 2025)
The study specifically, focused on identifying maintenance factors affecting productivity of the primary machines, identifying potential causes of primary machines failures and develop Maintenance Model and Maintenance Management System (MMS). The study was conducted through adoption of qualitative approach for data collection and quantitative for quantifying the problem. The most significant factors were found to be: organization and human resources, management, material management and equipment & machinery. Model development, test and validation by using most significant identified factors were analysed using Statistical Package for Social Sciences (SPSS). Validation of the model confirmed that, the developed models are valid and reliable because the variation between actual and predicted productivities from the year 2012/13 and year 2013/14 are very small; account to 3% & 2% and 5% & 4% respectively. The researchers recommend maintenance management system for the best practise at the workshops. From the findings, the study recommends that, the responsible organization can adopt the developed maintenance model and system in order to improve productivity of the primary machines at the workshops.